Pricing strategy selection for the sharing platform with heterogeneous laborers. (July 2022) - Nie, Tengfei; Guan, Shuhan; Du, Shaofu; Zhu, Siyuan
Highlights: A game-theoretic framework is built for analyzing labor-sharing mechanisms. Laborer-pricing and bargaining-pricing strategies are considered. Labor-sharing platform provides an authentication and charging. Two pricing strategies have their scope of application. Charging mechanism is affected by labors proportion and services quality. Abstract: In recent years, labor-sharing platforms have attracted widespread attention, and platforms such as Eatwith and ZBJ (ZBJ.com) have developed rapidly. The platforms connect labor providers and buyers by charging a fee. Although most labor-sharing platforms are structured in the same way, they have no clear, dominant pricing strategy. Some platforms adopt a labor-pricing strategy (LP strategy), while others adopt a bargaining-pricing strategy (BP strategy). Buyers can decide whether to purchase services on the platform based on their valuations. Laborers can offer services and decide whether to sell on the platform. In this research, we consider a platform that contemplates labor-sharing and designs its optimal pricing strategy by accounting for the two-sided trade-off between time savings and clarity in service quality. We also consider whether laborers or buyers should pay to connect to the platform under the BP strategy. First, our research shows that the impact of the platform's commission rate on the price under the BP strategy is nonmonotonic. In addition, we find that the market composition of labor and service quality can affect the labor-sharing platform's pricing strategy. Specifically, the LP strategy does not always perform well, explaining why some labor-sharing platforms adopt the BP strategy in practice. Finally, we demonstrate that the labor-sharing platform should choose different profit methods to maximize profits under different circumstances when adopting the BP strategy in the extension model.